Jordan : Fifth Post-Program Monitoring Discussions; Staff Report; and Press Release on the Executive Board Consideration. (IMF Staff Country Reports; Country Report ;, 2007)
This paper focuses on the Fifth Post-Program Monitoring Discussions with Jordan. Jordan's economic performance remains strong. Growth is robust, core inflation is contained, the current account deficit is narrowing, reserves are comfortable, and the fiscal situation continues to improve. The Fifth Post-Program Monitoring Discussions focused on a large current account deficit, still high public debt, and rapid credit growth. The authorities consider the outlook for the Jordanian economy as strong, including on growth, inflation, and the current account.